Coin Rotation Task: A Valid Test for Manual Dexterity in Multiple Sclerosis. Issue 11 (1st November 2014) - Heldner, Mirjam R.; Vanbellingen, Tim; Bohlhalter, Stephan; Mattle, Heinrich P.; Müri, René M.; Kamm, Christian P.
Abstract : Background: Impaired manual dexterity is frequent and disabling in people with multiple sclerosis (MS). Therefore, convenient, quick, and validated tests for manual dexterity in people with MS are needed. Objective: The aim of this study was to validate the Coin Rotation Task (CRT) for examining manual dexterity in people with MS. Design: This was a cross-sectional study. Methods: A total of 101 outpatients with MS were assessed with the CRT, the Expanded Disability Status Scale (EDSS), the Scale for the Assessment and Rating of Ataxia (SARA), and the Modified Ashworth Scale (MAS); muscle strength and sensory deficits of the hands were noted. The concurrent validity and diagnostic accuracy of the CRT were determined by comparison with the 9-Hole Peg Test (9HPT). Construct validity was determined by comparison with a valid dexterity questionnaire. Multiple regression analyses were done to explore correlations of the CRT with the EDSS, SARA, MAS, muscle strength, and sensory deficits. Results: The CRT correlated significantly with the 9HPT ( r =.73, P <.0001), indicating good concurrent validity. The cutoff values for the CRT relative to the 9HPT were 18.75 seconds for the dominant hand (sensitivity=81.5%, specificity=80.0%) and 19.25 seconds for the nondominant hand (sensitivity=90.3%, specificity=81.8%); these values indicated good diagnostic accuracy. Furthermore, the CRT correlated significantly with the dexterity questionnaire ( r =−.49, P <.0001), indicating moderate construct validity. Multiple regression analyses revealed that the EDSS was the strongest predictor for impaired dexterity. Limitations: Most of the people examined had relapsing-remitting MS and EDSS scores of up to 7. Conclusions: This study validated the CRT as a test that can be used easily and quickly to evaluate manual dexterity in people with MS.